The Relationship Between Mothers' Knowledge, Attitude, and Actions in Early Stimulation of Infant Development Aged 3-12 Months at UPTD Puskesmas Mazo - Yusnidar Laoli; Elvina Sari Sinaga; Yuniko Tadawura; Yusrisarimurni Laia; Zsa Zsa Ivany; Zulaika Syahputri Harahap (Malahayati Nursing Journal, 2025)
ABSTRACT The growth and development phase of infants aged 3-12 months is a crucial stage that requires intensive attention and early stimulation to achieve optimal motor, cognitive, and emotional development. This study aims to examine the relationship between mothers' knowledge, attitudes, and practices concerning early stimulation and the developmental progress of infants aged 3-12 months within the UPTD Puskesmas Mazo working area, Mazo District, South Nias Regency. A correlational analysis method with a cross-sectional design was utilized in this research. The sample comprised 30 mothers with infants aged 3-12 months, selected through purposive sampling. Data collection was conducted using questionnaires and observations, followed by analysis with the Chi-Square statistical test to assess the relationships between the variables studied. The results reveal that most mothers are between 20-30 years old (66.7%), have completed high school education (40%), and are primarily housewives (63.3%). Additionally, 60% of mothers demonstrate a good level of knowledge, 86.7% possess a positive attitude towards early stimulation, and 86.7% engage in effective practices when providing stimulation to their infants. Bivariate analysis indicates a significant correlation between mothers' knowledge and early stimulation (p = 0.003), mothers' attitudes and early stimulation (p = 0.012), as well as mothers' practices and early stimulation (p = 0.003). The study concludes that higher levels of knowledge, positive attitudes, and effective practices among mothers in providing early stimulation are associated with better developmental outcomes for infants. Therefore, it is crucial to implement educational and counseling interventions to enhance awareness and improve early stimulation practices among mothers. The findings of this research can serve as a valuable resource for healthcare professionals aiming to enhance infant growth and development through optimal early stimulation practices. Keywords: Knowledge, Attitude, Actions, Early Stimulation, Infant Development. ABSTRAK Masa tumbuh kembang bayi usia 3-12 bulan merupakan tahapan penting yang membutuhkan perhatian intensif serta stimulasi dini agar tercapai perkembangan motorik, kognitif, dan emosional yang optimal. Penelitian ini bertujuan untuk mengevaluasi hubungan antara tingkat pengetahuan, sikap, dan perilaku ibu dalam memberikan stimulasi dini dengan perkembangan bayi berusia 3-12 bulan di wilayah kerja UPTD Puskesmas Mazo, Kecamatan Mazo, Kabupaten Nias Selatan. Metode yang digunakan dalam penelitian ini adalah analisis korelasi dengan pendekatan transversal. Sampel terdiri dari 30 ibu yang memiliki bayi berusia 3-12 bulan, yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui angket dan observasi, kemudian dianalisis menggunakan uji statistik Chi-Square untuk mengevaluasi hubungan antara variabel yang diteliti. Hasil penelitian menunjukkan bahwa sebagian besar ibu berada dalam kelompok usia 20-30 tahun (66,7%), memiliki pendidikan tingkat SMA (40%), dan mayoritas berprofesi sebagai ibu rumah tangga (63,3%). Sebanyak 60% ibu memiliki pengetahuan yang baik mengenai stimulasi dini, 86,7% menunjukkan sikap positif terhadap stimulasi dini, dan 86,7% melaksanakan tindakan yang baik dalam memberikan stimulasi kepada bayi mereka. Analisis bivariat menunjukkan adanya hubungan yang signifikan antara tingkat pengetahuan ibu dengan stimulasi dini (p = 0,003), sikap ibu dengan stimulasi dini (p = 0,012), serta perilaku ibu dengan stimulasi dini (p = 0,003). Hasil penelitian ini menegaskan bahwa semakin tinggi pengetahuan, sikap, dan perilaku ibu dalam memberikan stimulasi dini, maka perkembangan bayi akan semakin optimal. Oleh karena itu, intervensi berupa edukasi dan penyuluhan mengenai pentingnya stimulasi dini sangat diperlukan guna meningkatkan kesadaran serta praktik stimulasi yang tepat bagi bayi. Diharapkan hasil penelitian ini dapat menjadi referensi bagi tenaga kesehatan dalam upaya peningkatan kualitas tumbuh kembang bayi melalui pemberian stimulasi dini yang optimal.            Kata Kunci : Pengetahuan, Sikap, Tindakan, Stimulasi Dini, Perkembangan Bayi